If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + -2) = 6 + -3y Reorder the terms: -3(-2 + x) = 6 + -3y (-2 * -3 + x * -3) = 6 + -3y (6 + -3x) = 6 + -3y Add '-6' to each side of the equation. 6 + -6 + -3x = 6 + -6 + -3y Combine like terms: 6 + -6 = 0 0 + -3x = 6 + -6 + -3y -3x = 6 + -6 + -3y Combine like terms: 6 + -6 = 0 -3x = 0 + -3y -3x = -3y Solving -3x = -3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-3'. x = y Simplifying x = y
| 2x+c=11c | | x=9-(x-5) | | 7-6x-7x=-149 | | 5h-30=8h | | 5(3-3-3t)=30 | | -(2x+3)=3x-1 | | (4x-9)+8(2x+3)-7x=0 | | 4.4t-2.9=-1.7+3.2 | | 36-y=-12 | | 16t^2-122t+192=0 | | y=(9-y)-5 | | 65x=54 | | 5x+3+6x+1=240 | | 3m^2+19m+16=0 | | 7(6-2a)=5(-3+a) | | -8-8t=3(2t-1) | | 6.5t+15=9.7+43.8 | | 144=11c-(-26) | | -10+3x-2x=-19 | | 7xy+2xy+3xy= | | 54x+54=11x | | y=(9-1)-5 | | -2x-(3x-8)=-2x-2 | | 3(.7)-4(.7)+1=5(.7)+2+3 | | 36x^4-49y^4= | | 8x+3x=9+12x | | 2(3t-5)-3(4t+1)= | | 2-m=17 | | -2.7+3.6=-5.8x+0.5 | | X+1-2x=-1 | | 9b-36=15b-10 | | -4x=6 |